Mechanical Behavior of the Novel Gradient Concrete Tower of a Cable-Stayed Bridge - Wang, Zuo-Cai; Duan, Da-You; Wang, Shu-Hang; Mo, Ye; Yin, Yong-Gao (Frontiers in Materials, 2021)
In this paper, the novel gradient concrete is innovatively applied to the bridge towers of Chizhou Yangtze River Bridge to solve the cracking and insufficient durability problems of concrete towers. Fiber-reinforced concrete is used in the outer functional area of the bridge tower, to significantly improve its crack resistance during construction and service. Moreover, the integrated design of anti-cracking and mechanical properties of tower materials is achieved. To study the performance of the novel functional gradient concrete (FGC) tower, the mechanical properties of the FGC tower material are tested, and the overall finite element stress is analyzed. Based on the material properties, the mechanical behavior of the cable-stayed bridge tower is studied. The temperature and stress of the FGC tower during the generation of the hydration heat are compared with that of the ordinary concrete tower. The crack resistance of the FGC tower is analyzed by the finite element method. The results show that the FGC tower has good mechanical properties and durability for the cable-stayed bridge towers.